APLIKASI MODEL COOPERATIVE LEARNING DALAM PEMBELAJARAN TEMA TANAMAN CIPTAAN ALLAH SUB TEMA TANAMAN SAYUR - Fasicha (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Keagamaan Islam UNUGHA Cilacap, 2022)
Early Childhood Education is a level of education before the basic education level which is a coaching effort aimed at children from birth to the age of six which is carried out through the provision of educational stimuli to help physical and spiritual growth and development so that children have readiness to enter further education, which is held on formal, non-formal and informal pathways. Early childhood development includes religious and moral, physical, cognitive, linguistic and social emotional values. Early Childhood Education is a level of education before the basic education level which is a coaching effort aimed at children from birth to the age of six which is carried out through the provision of educational stimuli to help physical and spiritual growth and development so that children have readiness to enter further education, which is held on formal, non-formal and informal pathways. Early childhood development includes religious and moral, physical, cognitive, linguistic and social emotional values.